Consensus statement on the content of clinical reasoning curricula in undergraduate medical education. (1st February 2021) - Cooper, Nicola; Bartlett, Maggie; Gay, Simon; Hammond, Anna; Lillicrap, Mark; Matthan, Joanna; Singh, Mini; ,
Abstract: Introduction: Effective clinical reasoning is required for safe patient care. Students and postgraduate trainees largely learn the knowledge, skills and behaviours required for effective clinical reasoning implicitly, through experience and apprenticeship. There is a growing consensus that medical schools should teach clinical reasoning in a way that is explicitly integrated into courses throughout each year, adopting a systematic approach consistent with current evidence. However, the clinical reasoning literature is 'fragmented' and can be difficult for medical educators to access. The purpose of this paper is to provide practical recommendations that will be of use to all medical schools. Methods: Members of the UK Clinical Reasoning in Medical Education group (CReME) met to discuss what clinical reasoning-specific teaching should be delivered by medical schools ( what to teach). A literature review was conducted to identify what teaching strategies are successful in improving clinical reasoning ability among medical students ( how to teach). A consensus statement was then produced based on the agreed ideas and the literature review, discussed by members of the consensus statement group, then edited and agreed by the authors. Results: The group identified 30 consensus ideas that were grouped into five domains: (1) clinical reasoning concepts, (2) history and physical examination, (3) choosing and interpreting diagnostic tests, (4) problem identification and management, and (5) shared decision making. The literature review demonstrated a lack of effectiveness for teaching the general thinking processes involved in clinical reasoning, whereas specific teaching strategies aimed at building knowledge and understanding led to improvements. These strategies are synthesised and described. Conclusion: What is taught, how it is taught, and when it is taught can facilitate clinical reasoning development more effectively through purposeful curriculum design and medical schools should consider implementing a formal clinical reasoning curriculum that is horizontally and vertically integrated throughout the programme.